2013
DOI: 10.1002/smll.201201069
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Uptake and Toxicity of Ag and CuO Nanoparticles: A Comparison Between Nanoparticles and their Corresponding Metal Ions

Abstract: CuO-nano toxicity is predominantly mediated by intracellular uptake and subsequent release of copper ions, whereas no toxicity is observed for Ag-nano due to low release of silver ions within short time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
196
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(222 citation statements)
references
References 41 publications
22
196
4
Order By: Relevance
“…The cytotoxicity of CuO NPs on Caco2 cells showed a number of similarities with the results observed by Cronholm et al (2013). There are no clear aggregates on the TEM image (Fig.…”
Section: Resultssupporting
confidence: 78%
“…The cytotoxicity of CuO NPs on Caco2 cells showed a number of similarities with the results observed by Cronholm et al (2013). There are no clear aggregates on the TEM image (Fig.…”
Section: Resultssupporting
confidence: 78%
“…mechanism, which explained how AgNPs facilitated the release of free toxic silver ions in cells, where the particles entered and were then ionized. [32][33][34] Accordingly, intracellular silver ion release greatly contributed to the antibacterial activities of AgNPs. The surface ligand might also regulate this process in the similar way to what happened in vitro, thus explaining the toxicity order of the four tested AgNPs described earlier.…”
Section: E Coli the Results Inmentioning
confidence: 99%
“…and acidic condition of the organelle (lysosome, etc.) might facilitate the oxidation of the silver core, 32 potentially inducing the generation of more silver ions and ROS, which could trigger the corresponding biological effects, such as antibacterial activities. With regard to the quantification for the percentage of particulate effect, this is still challenging due to the complexity of the antibacterial mode of AgNPs, and the hot debate on this question continues in the related toxicological studies.…”
Section: E Coli the Results Inmentioning
confidence: 99%
“…Many studies have focused on CuONP-induced cytotoxicity and corresponding mechanisms in human lung epithelial cells. 11,12,[17][18][19] Oxidative stress and autophagy have been reported to play vital roles in CuONPinduced cytotoxicity. 12, 18 Hanagata et al reported that CuONP exposure upregulated genes involved in mitogen-activated protein kinase (MAPK) pathways while downregulating genes involved in cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%